2012
DOI: 10.1074/jbc.m112.396416
|View full text |Cite
|
Sign up to set email alerts
|

S100A6 Amyloid Fibril Formation Is Calcium-modulated and Enhances Superoxide Dismutase-1 (SOD1) Aggregation

Abstract: Background:The calcium and zinc binding S100A6 protein is overexpressed in ALS and Alzheimer's disease. Results: S100A6 aggregates into fibrils under physiological conditions, a process repressed by calcium. Native S100A6 enhances aggregation of SOD1, a hallmark of ALS. Conclusion: S100A6 is a novel amyloidogenic protein and its aggregation is modulated by calcium. Significance: S100A6 aggregation elicits yet unconsidered roles in human pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…This has precisely been demonstrated for S100A6, which was shown to undergo amyloid β-aggregation both at neutral and acidic pH, albeit with very distinct timescales [23]. Indeed, S100A6 has been included in the present study as a control and was further analyzed in respect to structural changes occurring upon acidification.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…This has precisely been demonstrated for S100A6, which was shown to undergo amyloid β-aggregation both at neutral and acidic pH, albeit with very distinct timescales [23]. Indeed, S100A6 has been included in the present study as a control and was further analyzed in respect to structural changes occurring upon acidification.…”
Section: Resultssupporting
confidence: 60%
“…Recently, we showed that S100A6 forms amyloid fibrils under physiological conditions and that the native protein nucleates Cu/Zn superoxide dismutase (SOD1) fibrillation, shortening its nucleation process. These findings suggest a novel role for S100A6 aggregation in human neuropathologies, particularly in amyotrophic lateral sclerosis (ALS) [23]. Taking into account this background, we herein report a study in which we have analyzed seven human S100 proteins for relationships between aggregation propensity, disordered regions and amyloid formation, combining computational and biophysical tools.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, S100A6 protein's capacity to form fibrils was also affected by calcium (Botelho et al . ). So far, there is no proof of an in vivo interaction between these two proteins or its association with a diseased‐state.…”
Section: Discussionmentioning
confidence: 97%
“…The protein appears to be regulated by calcium which binds to two EF-hand calcium binding sites within the protein. The binding of calcium is thought to induce conformational change in the protein which is involved in the regulation of a number of processes including cell proliferation and differentiation, calcium homeostasis, cell degeneration, and cytoskeletal dynamics via signal transduction pathways (21,22).…”
Section: Resultsmentioning
confidence: 99%